확장된 기술수용모델을 적용한 실시간 화상강의 이용의도에 영향을 미치는 요인 연구 - 이장석(Jang-Suk Lee); 양승현(Seoung-Hyun Yang); 송병원(Byoung-Weon Song) (한국콘텐츠학회 논문지, 21(1), 2021)
The influence of COVID 19 has a direct impact on the education field. In the situation where non-face-to-face classes are inevitably required, interest in the learning satisfaction and intention to use real-time video conferencing is increasing. This study analyzed the effects of learner-teacher interaction, social presence, availability, self-efficacy and academic engagement as video conferencing characteristics and learner's characteristics on perceived usefulness, perceived ease of use, learning satisfaction and intention to use video conferencing. The results of this study showed that learner-teacher interaction, availability, and self-efficacy had a positive effect on perceived ease of use, and all variables except availability had a positive effect on perceived usefulness. Also, perceived usefulness and ease of use were factors that increased learning satisfaction and video conferencing use intention, and learning satisfaction was identified as variables that increased video conferencing use intention. This study has significance in that it provided various theoretical and practical implications for real-time video conferencing which will be used in many educational fields in the future through empirical analysis. COVID 19의 영향이 교육계에도 직접적인 영향을 미치고 있다. 특히, 비대면 수업이 선택이 아닌 필수가 된 상황에서 실시간 화상강의에 대한 학습자의 만족과 이용의도를 높일 수 있는 방안에 대해 관심이 높아지고 있다. 본 연구에서는 화상강의 특성으로서 학습자-교수자 간 상호작용성, 사회적 실재감, 이용가능성, 자기효능감, 참여정도가 인지된 유용성과 이용 용이성, 학습 만족과 화상강의 이용의도에 영향을 미치는지 분석하였다. 연구결과, 인지된 이용 용이성에는 학습자-교수자 상호작용성과 이용가능성, 자기효능감이 정적인 영향을 미치는 것으로 나타났으며, 인지된 유용성에는 이용가능성을 제외한 모든 변인이 정적인 영향을 미치는 것으로 확인되었다. 또한, 인지된 유용성과 이용 용이성은 학습 만족과 화상강의 이용의도를 높이는 요인인 것으로 확인되었으며, 학습 만족 역시 화상강의 이용의도에 정적인 영향을 미치는 주요 변인인 것으로 나타났다. 본 연구는 실증적인 분석을 통해 향후 많은 교육 현장에서 활용하게 될 실시간 화상강의에 대해 여러 이론적, 실천적 시사점을 제공했다는 점에 의의가 있다.